A comprehensive longitudinal study of gut microbiota dynamic changes in laying hens at four growth stages prior to egg production - Seojin Choi; Eun Bae Kim (Animal Bioscience, 2023)
Objective The poultry industry is a primary source of animal protein worldwide. The gut microbiota of poultry birds, such as chickens and ducks, is critical in maintaining their health, growth, and productivity. This study aimed to identify longitudinal changes in the gut microbiota of laying hens from birth to the pre-laying stage. Methods From a total of 80 Hy-Line Brown laying hens, birds were selected based on weight at equal intervals to collect feces (n = 20 per growth) and ileal contents (n = 10 per growth) for each growth stage (days 10, 21, 58, and 101). The V4 regions of the 16S rRNA gene were amplified after extracting DNA from feces and ileal contents. Amplicon sequencing was performed using Illumina, followed by analysis. Results Microbial diversity increased with growth stages, regardless of sampling sites. Microbial community analysis indicated that Firmicutes, Proteobacteria, and Bacteroidetes were the dominant phyla in the feces and ileal. The abundance of Lactobacillus was highest on day 10, and that of Escherichia-shigella was higher on day 21 than those at the other stages at the genus level (for the feces and ileal contents; p<0.05). Furthermore, Turicibacter was the most abundant genus after changing feed (for the feces and ileal contents; p<0.05). The fecal Ruminococcus torques and ileal Lysinibacillus were negatively correlated with the body weights of chickens (p<0.05). Conclusion The gut microbiota of laying hens changes during the four growth stages, and interactions between microbiota and feed may be present. Our findings provide valuable data for understanding the gut microbiota of laying hens at various growth stages and future applied studies.